LAN monitoring and management tool (LMMT) / Muhammad Izwan Idris - Muhammad Izwan, Idris (2005)
LAN Monitoring and Management Tool (LMMT) is an application that monitor and manages interconnected computer via a network. This tool is design for small to medium company that is running their performance in Local Area Network (LAN). The goal is to create a remote application, which overs the management of the connected computer and monitor the traffic across a network. This application obtains a maximum of capabilities and efficiency, which allows the administrator to monitor all the traffic flow in their network, controls other computer in a systematic way. This application development based on the users need, which is focus on network engineer and administrator. It may help these target users to gain the information of the activity running in their network environment and manage it efficiently. This application will be developing base on Windows Packet Capturing (WinPcap), Windows Socket (Winsock) and Windows Management Instrumentation (WMI) technology using Visual Basic. All are rich in queries and provide powerful technologies.